The application of case-based reasoning in construction management research: An overview - Hu, Xin; Xia, B.; Skitmore, M.; Chen, Q. (Elsevier BV, 2016)
Case-based reasoning (CBR) has been widely adopted in construction management (CM) research due to the similar mind-sets of CBR and CM problem solving. However, to date, there has been no systematic review of CBR applications in previous CM studies, raising the question of what is the current status quo of CBR applications in CM research? By using the method of content analysis, this study provides a comprehensive literature review of CM CBR articles published between 1996 and January 2015. It is found that the popularity of CBR applications in CM research is increasing, especially after 2006, with a majority emanating from South Korea. In addition, 17 CBR application fields are identified, with the primary research interests focusing on construction cost estimation, construction tendering, bidding and procurement, and environment and sustainability management. Issues in previous CBR model developments are also identified, mainly related to model hypothesis-testing, reuse of case outcomes, selection of model development methods, use of derivational analogy and automated implementation, together with future research suggestions and directions. This study helps provide CM academics and practitioners with a more comprehensive understanding of the development of CBR applications and implications for future studies.